Rapid assessment of the osteogenic capacity of hydroxyapatite/aragonite using a murine tibial periosteal ossification model - Emma Steijvers; Yunshong Shi; Hong Lu; Weixin Zhang; Yitian Zhang; Feihu Zhao; Baichuan Wang; Louise Hughes; Jake E. Barralet; Giulia Degli-Alessandrini; Igor Kraev; Richard Johnston; et al. (Bioactive Materials)
Biomaterials are widely used as orthopaedic implants and bone graft substitutes. We aimed to develop a rapid osteogenic assessment method using a murine tibial periosteal ossification model to evaluate the bone formation/remodelling potential of a biomaterial within 2–4 weeks. A novel hydroxyapatite/aragonite (HAA) biomaterial was implanted into C57BL/6 mice juxtaskeletally between the tibia and tibialis anterior muscle. Rapid intramembranous bone formation was observed at 14 days, with 4- to 8-fold increases in bone thickness and callus volume in comparison with sham-operated animals (p < 0.0001), followed by bone remodelling and a new layer of cortical bone formation by 28 days after implantation. The addition of zoledronate, a clinically-utilised bisphosphonate, to HAA, promoted significantly more new bone formation than HAA alone over 28 days (p < 0.01). The osteogenic potential of HAA was further confirmed by implanting into a 3.5 mm diameter femoral cancellous bone defect in rats and a 5 mm diameter femoral cortical bone defect in minipigs. To understand the biodegradation and the cellular activity at the cell/biomaterial interfaces, non-decalcified specimens were resin embedded and sections subjected to combined scanning electron microscopy (SEM)/electron backscatter diffraction (EBSD)/energy dispersive X-ray spectrometry (EDS) analysis. We conclude that murine tibial periosteal ossification is a novel method for rapid assessment of the interaction of bioactive materials with osteogenic tissues. This study also highlights that combining calcium carbonate with hydroxyapatite enhances biodegradation and osteogenesis.